Bimbingan Pra Nikah dan Implikasinya Terhadap Pembentukan Keluarga Maslahah: Studi Kasus di KUA Pajarakan - Nofa Taufani Warda; Fathullah Rusly; Vita Firdausiyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Pre-marital guidance is an important approach in preparation for marriage and a process of accompanying husbands and prospective wives before marriage in order to help them find happiness in their marriages and households. This journal digs deeper into pre-marriage counselling and its implications for family formation. The role of premarital counseling in forming healthy relationships, effective communication, a deeper understanding of the roles of husbands and wives in Islam, as well as preparation to face the challenges that may arise in marriage. By strengthening religious understanding, effective communication, preparedness for challenges, and promoting well-being and an active role in society, pre-marriage guidance can be a strong foundation for forming a family that brings benefits in society. As for the results obtained from this study: 1) Implementation of pre-marriage guidance for the prospective bride for 2 days, coordinated by the Ministry of Religious Affairs of the probolinggo district, its applicant is the KUA District 2) Couples who follow the marriage guide for two days to acquire science or knowledge to start a life in the staircase, which initially the candidate bride believed that the capital of marriage was only mental and financial.